Why Eastern Bloc Countries Dominated the Gymnastics Field in Sydney - Apatow, S. (coachesinfo.com, 2000)
Despite the economic collapse of the Eastern Bloc countries, Russia and Romania dominated the gymnastics field in Sydney. Some of the most striking contrasts between their athletes and those representing the international field was their classical ballet based precision alignment and integration into technical movement. It was clear that the Eastern Bloc emphasis on classical ballet based choreography training contributed to the success of their teams at the Olympics. In Eastern Bloc development programs, a selection process is used to locate children who have natural joint flexibility and body mechanics which are considered prerequisite for future progress in ballet or Olympic competition. Those selected then enter into a development program which integrates classical ballet based choreography training as a foundation for the correct execution of technical sports specific movement. Classical ballet training is considered the most advanced movement mechanics training in the world, providing a foundation for the development of joint strength, postural alignment and precision control of the human frame in space. In Eastern Bloc programs, approximately 45 minutes per day is committed to this training, 6 days per week. In the United States, all children have the opportunity to enter a gymnastics or ballet program regardless of limitations with joint flexibility or body mechanics. This scenario presents a variety of challenges which require special attention, accentuated stretch programs and exercise sequences which address the anatomical limitations of the student. The role former Eastern Bloc coaches, Olympic gold medalists, ballet teachers and dancers play in arts and sports development programs in the United States is significant. Many of these individuals represent the gifted fortunate few, who in their countries excelled in their disciplines. Their teaching methods are based on work with those that possess the ideal physical attributes, not on the adaptation of an elite program for the vast majority of children who have structural and functional limitations. An additional challenge is that in Eastern Bloc countries, an entire coaching staff may be responsible for 6-10 full time potential olympic athletes whereas in the US upwards of 2000 children can be enrolled in one program. Time limitations in US programs, especially early developmental levels, limit the capacity of many programs to integrate classical ballet based choreography training, leaving this crucial developmental prerequisite for students which progress to advanced levels. Ballet Training & Gymnastics in the United states A former Eastern Bloc, now U.S. National Team coach shared that in the United States, gymnastics coaches are not generally open to discussion regarding the subject of classical ballet training. A common perception is that ballet and gymnastics represent two different forms of training. This perspective is in direct contrast to the mandatory classical ballet based choreography training which is required for all athletes in Eastern Bloc development programs. When consensus is achieved to integrate this training, the athletes are then subject to common challenges that exist in U.S. based classical ballet training programs. One such problem relates to forced vs. natural turnout of the feet . Forced turnout occurs when the foot is externally rotated beyond correct knee, ankle and foot alignment (Parent Advisory www.sportballet.com/advisory). This malalignment pattern, when introduced repetitively during the crucial years of child development (before epiphyseal joint plate closure) can lead to serious alignment problems and compensatory changes in the lower extremities and spine. Another problem area relates to shoulder flexibility which is a prerequisite for correct alignment of the upper extremity. Incorrect alignment in classical ballet training is directly transferred to sports specific movement. A Russian teacher and former student from the Bolshoi (Moscow) and Vaganova (Leningrad) Academies of Dance shared that the vast majority of the children participating in U.S. ballet programs are forcing unnatural positions. Many Russian ballet teachers have understood these problems for decades, but are unable to address them because they represent an unpopular subject. Postural alignment as illustrated in correct classical ballet training is the reference point for the most stable, balanced, integrated relationship of the spine and extremities that exists. If a movement is executed at any developmental level with incorrect alignment, the associated spine and extremities will strengthen incorrectly, leading to joint instability and lack of precision control of the human frame in space. As for Sydney, perhaps one of the most significant lessons pointed to our need to reexamine the importance of classical ballet based training as an essential building block for the elite development program.